PELATIHAN PENGEMBANGAN DIRI SENI TARI DI SMA NEGERI 1 BATANG ANAI - Aziza Safitri M; Zora Iriani; Desfiarni Desfiarni (FBS Universitas Negeri Padang, 2018)
AbstractThis research aimed to reveal and describe the training of self-development dance arts at SMA N 1 Batang Anai. The type of this research was qualitative research with descriptive method analysis. The research object was female students of SMA N 1 Batang Anai at grade XI IPS 1, XI IPS 2, XI IPS 3, XI IPS 4 and XI IPS 5 in even semester (January-June) academic year 2017/2018 who joined self-development. The instrument used in this research was the researcher itself. The types of data in this study were the primary and secondary data. The technique of data collection was done by documents study, observation, interview, and documentation. The result of the research showed that the training of self-development in the dance arts ran well. Although the students’ interest in dancing was very low which only 12 from 21 students who registered. Those 12 female students who attended the training had a good ability in dance since they practiced dance, they focused and were serious. Moreover, they were also able to perform Pasambahan dance and performed it on school event namely Art Performance in SMA N 2 Batang Anai that was held on Saturday, 30th June 2018. Keywords: Training, Self-Improvement, Dance